Biotic assemblages from Early Cretaceous lacustrine systems in the San Luis Basin, mid-western Argentina - Arcucci, Andrea Beatriz (2015)
Significant paleobiological data has emerged from the San Luis Basin (Early Cretaceous, Aptian-Albian in Central Argentina) during the last decades. Two units in this basin include lake paleo-environments with important fossil contents in an excellent state of preservation that could be considered as Konservat Lagerstätten deposits. The association of fossil leaves and pollen grains from the La Cantera Formation is one of the most ancient and complete angiosperm records in South America and the bryophyte association of the same unit constitutes one the most complete records of its type in Argentina. Insects from five different orders have been identified in this association, and three endemic species of aquatic insects from the La Cantera Formation have been described as belonging to the Notonectidae and Corixidae families, including the oldest member of the Anisopinae subfamily. The Pterodaustro guinazui association from the Lagarcito Formation is one of the few fossil associations recorded worldwide from which it is possible to make studies on the life history parameters of pterosaurs-like growth patterns and ontogeny. The Pleuropholid fish from the Lagarcito Formation are the only record of this group in Argentina and the second in South America. Several new species of ostracods and conchostracea have also been recorded from the same units. Despite the amount of paleontological information now available from the San Luis basin, much work remains to be done on these fossil associations and the interpretation of their depositional environments.